The Development of the International Organization and Organizational Sociology Theories and Perspectives. Part 1-The Origin - Medani Bhandari (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2019)
This paper provides an overview of how international organizations were formed, for what purposes and how their structure has been changed. The distinction between formal organizational studies and studies of international organizations is minimal, because both help to widen the idea of creating an original position for better combinations of favorable circumstances or situations in human affairs. The chapter will explain, the origin of the term international organization (OR); historical roots of or studies; and define or; analyze the types of ORs in the contemporary world; reveals the relationship between the international relation (IR) and regime theories application in the OR’s studies; and the impact of the globalization. The chapter also unveils the relationships between organizational sociology and OR and finally it gives a general outline on the application institution theory in the study of OR following a brief summary. Organizations have the ability of inspiring and bringing people in concert to achieve combined goals. They are accountable for determining the intelligence needed to meet their goals. This chapter provides a glimmer of international organizations theory, origin, historical account, definitions and utilization of contemporary academic world intertwined with the international relations, regime and globalization as well as the organizational sociological theories and perspectives can be utilized to study of international organizations. This chapter will help to understand the historical account of international organization, pedagogical development and contemporary theories and practices of international organizations and organizational sociology.